Incidence of Ventral Hernia Repair after Open Abdominal Aortic Aneurysm and Open Aortofemoral or Aortoiliac Bypass Surgery: An Analysis of 17, 594 Patients in the State of New York. Issue 8 (August 2018) - Altieri, Maria S.; Yang, Jie; Jones, Tyler; Voronina, Angelina; Zhang, Mengru; Kokkosis, Angela; Talamini, Mark; Pryor, Aurora D.
The purpose of our study was to evaluate the rate of ventral hernia repair (VHR) after open abdominal aortic anneurysm in New York State compared with the rate of VHR after open abdominal aortic bypass procedures. The Statewide Planning and Research Cooperative System database was queried for all abdominal aortic aneurysm (AAA) and bypass procedures performed between 2000 and 2010. Social security death index was used to identify patients who died. The cause-specific Cox proportional hazard model was applied to compare the risk of having follow-up VHR between patients with AAA and bypass with death as a competing risk event. A multivariable model was used to explore independent relationship with the risk of having follow-up ventral hernia after adjusting for other factors. There were 9314 patients who underwent open AAA repair, 739 (7.93%) of which had subsequent VHR. Comparatively, 8280 patients underwent aortofemoral or aortoiliac bypass procedures, with 480 (5.8%) undergoing subsequent VHR. The observed one-year, five-year, and 10-year VHR rates for AAA versus bypass were 2.8 versus 1.8 per cent, 10.0 versus 8.0 per cent, 10.7 versus 9.38 per cent, respectively. After controlling for all other factors, patients undergoing AAA repair were more likely and elderly patients were less likely to undergo VHR (P < 0.0001). Patients with serious comorbid conditions such as valvular disease, diabetes mellitus, and neurologic disorders were less likely to undergo subsequent VHR controlling for other factors. VHR after AAA procedures is more common compared with bypass procedures for occlusive disease. Because this patient population has significant comorbidity, prophylactic mesh placement may play a role in preventing necessity for future procedures.